Sentarse a la mesa del Señor. Metaforizaciones y conflictos en La última cena de Tomás Gutiérrez Alea (Altre Modernità, 2011)
La última cena by Gutiérrez Alea is based on an actual event that took place in Cuba: one Holy Thursday at the end of the Eighteen century the owner of a sugar plantation invites twelve of his slaves to dinner and shows them the path to salvation through the message of Christian Redemption. In particular, the film shows how during the Easter rite the messianic event and the metaphoric language of salvation lead to shifts in meaning that the slaves interpret as the concrete possibility for them to be free. The sacred of the liturgical act as an “action” that can be performed by the guests at the Lord’s table in order to reach freedom is reproduced by the very cinematographic language. Actually, the slaves oppose to the Christian account an “open word”, thus debunking the project of disciplining them and stirring a rebellion in which the contamination of the sacred with the profane becomes the epiphany of a new life: no more a celestial one, but a worldly and free life in the isle of Cuba.